Cardiovascular rate pressure product is associated with NfL in older adults at risk for AD - Chinenye C. Odo; Joe Strong; Sarah R. Lose; Yue Ma; Catherine L. Gallagher; Barbara B. Bendlin; Henrik Zetterberg; Kaj Blennow; Cynthia M. Carlsson; Gwendlyn Kollmorgen; Clara Quijano‐Rubio; Nathaniel A. Chin; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Elevated cardiovascular rate pressure product (RPP) has been shown to predict cardiovascular mortality and is associated with poor cognitive test performance among older adults. However, it is unclear how RPP is related to the cerebrospinal fluid (CSF) biomarkers of neurodegeneration and neuroinflammation. METHODS RPP was cross‐sectionally evaluated as a predictor of CSF biomarker levels in a cohort of 310 cognitively unimpaired late‐middle‐aged adults at risk for Alzheimer's disease. The primary outcomes were CSF levels of α‐Synuclein, glial fibrillary acidic protein, neurofilament light (NfL), soluble triggering receptor expressed in myeloid cells 2, and total tau. Further analyses examined amyloid beta (Aβ)42/Aβ40, phosphorylated tau 181 (pTau181), and pTau181/Aβ4. RESULTS RPP was positively associated with NfL (β = 0.006, R2 = 0.411, p = 0.012, but Bonferroni‐corrected p ≤ 0.006) and not with other CSF biomarkers of neurodegeneration and neuroinflammation investigated in this sample. DISCUSSION A high myocardial oxygen demand at rest may be related to neuronal death and axonal degeneration in cognitively unimpaired late‐middle‐aged adults. Highlights We explored the relationship between RPP and CSF analytes. Higher RPP was associated with higher NfL but not other measured CSF biomarkers. HR was positively associated with NfL, whereas SBP was not.